Al2O3-SiCw-TiC composite ceramic composition, Al2O3-SiCw-TiC composite ceramic and preparation method of Al2O3-SiCw-TiC composite ceramic
By introducing TiC particles and SiCw whiskers into Al2O3-SiCw ceramics, the component ratio and sintering process are optimized, the problem of insufficient flexural strength of ceramic materials is solved, and higher flexural strength and fracture toughness are achieved, which is suitable for high-speed cutting processing.
Patent Information
- Application Number
- CN202411743250.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-18
AI Technical Summary
The existing Al2O3-SiCw ceramic materials have low flexural strength, which limits their application in high-speed cutting processing.
By introducing TiC particles with a particle size of no more than 800 nm and combining SiCw whiskers, the mass proportion of Al2O3, SiCw and TiC particles is optimized, and Al2O3-SiCw-TiC composite ceramics are prepared by vacuum hot press sintering process.
It significantly improves the flexural strength and fracture toughness of composite ceramics, improves the strength and toughness of materials, and extends the service life of the tool.
Smart Images

Figure CN119638463A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of ceramic technology, and in particular to an Al2O3-SiC w -TiC composite ceramic composition, Al2O3-SiC w -TiC composite ceramics and preparation method thereof. Background Art
[0002] In recent years, with the rapid development of high-end technology fields such as national defense, aerospace, and automobile manufacturing, mechanical manufacturing has achieved rapid development. As one of the most widely used processing methods in mechanical manufacturing, cutting is developing towards high cutting speeds, which puts higher requirements on tool materials. Ceramic tools have a simple production process, high strength, hardness, and melting point, and excellent wear resistance and high-temperature mechanical properties. They are suitable for high-speed cutting of cast iron, hardened steel, and high-temperature alloys. Ceramic tools greatly improve processing efficiency and are expected to become mainstream cutting tools.
[0003] Al2O3 ceramic tool materials are the most produced ceramic tools in the world due to their simple preparation process and excellent performance. They have been widely used in the cutting of automotive parts and high-temperature alloys. However, they have poor toughness and easy chipping during high-speed cutting, which limits their application in high-speed cutting. To this end, researchers often add whiskers to Al2O3 and use the whiskers to bridge, pin or deflect cracks in the Al2O3 matrix and pull out the whiskers to improve the toughness of Al2O3. SiC whiskers (SiC w) has the characteristics of high strength, high modulus and good chemical stability, and can play a good toughening effect. For example, the Chinese patent application with the patent application publication number CN114956846A discloses a method for preparing a SiC whisker toughened alumina ceramic tool material. Zhu et al. prepared Al2O3-25vol%SiCw by oscillatory pressure sintering (Zhu TB, Xie ZP, Han Y, et al. Improved mechanical properties of Al2O3-25vol%SiCw composites prepared by oscillatory pressure sintering [J]. Ceramics International, 2017, 43 (17): 15437-15441.). The above patents and studies all point out that SiC whiskers have a good toughening effect on the Al2O3 matrix, and Al2O3-SiCw ceramic material has become one of the most widely used ceramic tool materials. However, the presence of SiC whiskers hinders the sintering densification of ceramic materials, reduces the flexural strength of composite ceramics, and thus affects the service life of the tool. Summary of the invention
[0004] The main purpose of the present invention is to provide an Al2O3-SiC w -TiC composite ceramic composition, Al2O3-SiC w -TiC composite ceramics and preparation methods thereof to solve the problems of Al2O3-SiC in the prior art w Ceramics have the problem of low flexural strength.
[0005] In order to achieve the above object, according to one aspect of the present invention, there is provided an Al2O3-SiC w -TiC composite ceramic composition, in terms of mass percentage, the composition comprises: 5 to 15 wt% SiC w ; 5 to 15 wt% TiC particles; and the remainder Al2O3; wherein the particle size of the TiC particles does not exceed 800 nm.
[0006] Furthermore, the above composition comprises, by mass percentage: 10-15wt% SiC w , 5 to 10 wt% TiC particles and the balance Al2O3.
[0007] Furthermore, the above-mentioned Al2O3, SiC w The mass ratio of TiC particles to TiC particles is 0.79:(0.1-0.15):(0.05-0.1); and / or, the composition further comprises 1-5wt% of a sintering aid.
[0008] Furthermore, the sintering aid is MgO and / or Y2O3; and / or the particle size of the TiC particles is 40 to 500 nm.
[0009] Furthermore, the sintering aid is a combination of MgO and Y2O3, and the mass ratio of MgO to Y2O3 is 1 to 4:1; and / or the particle size of the TiC particles is 300 to 500 nm.
[0010] According to another aspect of the present invention, there is provided an Al2O3-SiC w -TiC composite ceramic preparation method, the preparation method comprises: the above-mentioned composition and solvent are sequentially mixed, dried and sintered to obtain Al2O3-SiC w -TiC composite ceramics.
[0011] Furthermore, the sintering is carried out in a vacuum hot pressing sintering furnace, and the sintering temperature is 1600-1750°C; and / or the sintering holding time is 0.5-3h; and / or the sintering hot pressing pressure is 15-35MPa; and / or the drying temperature is 70-110°C; and / or the drying time is 6-15h; and / or the volume ratio of the composition to the solvent is 1:15-50; and / or the mixing includes: ultrasonicating and ball milling the composition and the solvent in sequence, and then drying.
[0012] Furthermore, the ultrasonication time is 30 to 60 minutes; and / or the ball milling time is 4 to 16 hours; and / or the ball milling speed is 250 to 500 rpm.
[0013] According to another aspect of the present invention, there is provided an Al2O3-SiC w -TiC composite ceramics, the Al2O3-SiC w -TiC composite ceramics are prepared by the aforementioned preparation method.
[0014] Furthermore, the Al2O3-SiC w -The fracture toughness of TiC composite ceramics is 5.1~7.2MPa·m 1 / 2 ; and / or, Al2O3-SiC w -The flexural strength of TiC composite ceramics is 436~595MPa.
[0015] The technical solution of the present invention is applied to improve the flexural strength of the composite ceramic by introducing TiC particles with a particle size not exceeding 800nm. TiC particles can inhibit the growth of Al2O3 matrix grains and form a fine and evenly distributed grain structure, which is conducive to enhancing the strength of the material. At the same time, the excellent interface bonding between TiC and the Al2O3 matrix can effectively transfer loads and avoid crack propagation, thereby helping to improve the flexural performance of the composite ceramic. Normally, the addition of TiC easily leads to an increase in the brittleness of the ceramic, but the addition of TiC particles in this application is similar to that of SiC. w The synergistic effect of TiC particles can improve the fracture toughness of composite ceramics. The presence of TiC particles in the crack path can induce crack deflection, bridging and pinning effects, which in turn helps to increase the energy barrier for crack propagation, making it less likely for composite ceramics to undergo brittle fracture when subjected to external forces. w The mass proportion of TiC particles is within the above range, which helps to improve the interaction between the components, thereby helping to further improve the Al2O3-SiC w -Fracture toughness and flexural strength of TiC composite ceramics. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0017] Figure 1 The SEM photograph of the fracture of the ceramic material in Example 1 of the present application is shown;
[0018] Figure 2 The SEM photograph of the fracture of the ceramic material in Example 2 of the present application is shown;
[0019] Figure 3 The SEM photograph of the fracture of the ceramic material in Example 3 of the present application is shown;
[0020] Figure 4 The SEM photograph of the fracture of the ceramic material in Comparative Example 1 of the present application is shown. DETAILED DESCRIPTION
[0021] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0022] Terminology Explanation: SiC w It refers to SiC whisker material with a diameter of 0.1 to 0.6 μm and a length of 10 to 50 μm.
[0023] As analyzed in the background technology of this application, Al2O3-SiC w Ceramics have the problem of low flexural strength. In order to solve the above problem, the present application provides an Al2O3-SiC w -TiC composite ceramic composition, Al2O3-SiC w -TiC composite ceramics and preparation method thereof.
[0024] In a typical embodiment of the present application, an Al2O3-SiC w -TiC composite ceramic composition, in terms of mass percentage, the composition comprises: 5 to 15 wt% SiC w , 5 to 15 wt % TiC particles and the balance Al2O3; wherein the particle size of the TiC particles does not exceed 800 nm.
[0025] The introduction of TiC particles with a particle size of no more than 800nm helps to improve the flexural strength of the composite ceramic. TiC particles can inhibit the growth of Al2O3 matrix grains, forming a fine and evenly distributed grain structure, which is conducive to enhancing the strength of the material. At the same time, the excellent interface bonding between TiC and the Al2O3 matrix can effectively transfer loads and avoid crack propagation, thereby helping to improve the flexural performance of the composite ceramic. Normally, the addition of TiC easily leads to an increase in the brittleness of the ceramic, but the addition of TiC particles in this application is similar to that of SiC. w The synergistic effect of TiC particles can improve the fracture toughness of composite ceramics. The presence of TiC particles in the crack path can induce crack deflection, bridging and pinning effects, which in turn helps to increase the energy barrier for crack propagation, making it less likely for composite ceramics to undergo brittle fracture when subjected to external forces. w , TiC particles are within the above range, which helps to improve the interaction between the components and helps to maintain the Al2O3-SiC w -TiC composite ceramics have higher fracture toughness and further improve their flexural strength.
[0026] In order to further improve the Al2O3-SiC w -The flexural strength of TiC composite ceramics. In one embodiment of the present application, the above composition preferably includes: 10-15wt% SiC w , 5 to 10 wt% TiC particles and the balance Al2O3.
[0027] In one embodiment of the present application, the Al2O3, SiC w The mass ratio of the particles to TiC is 0.79:(0.1-0.15):(0.05-0.1); and / or, the composition further comprises 1-5wt% of a sintering aid.
[0028] Optimum control of Al2O3, SiC w The mass ratio of particles to TiC is within the above range, which helps to make Al2O3-SiC w -TiC composite ceramics further improve their flexural strength while having high fracture toughness. The addition of sintering aids helps to reduce the sintering temperature of composite ceramics and promote the densification of materials at lower temperatures, thereby reducing porosity and improving the comprehensive performance of materials.
[0029] In one embodiment of the present application, the sintering aid is MgO and / or Y2O3; and / or the particle size of the TiC particles is 40 to 500 nm.
[0030] It is preferred to control the type of sintering aid within the above range, which helps to further reduce the sintering temperature of the composite ceramic, thereby helping to reduce the porosity of the composite ceramic. It is preferred to control the particle size of the TiC particles within the above range, which helps to further inhibit the growth of Al2O3 matrix grains and form a finer and more evenly distributed grain structure, thereby helping to improve the flexural strength of the composite ceramic.
[0031] In one embodiment of the present application, the sintering aid is a combination of MgO and Y2O3, and the mass ratio of MgO to Y2O3 is 1 to 4:1; and / or the particle size of the TiC particles is 300 to 500 nm.
[0032] MgO and Y2O3, as sintering aids, can reduce the sintering temperature of composite ceramics during the sintering process and promote the densification of materials. It is preferred to control the mass ratio of MgO and Y2O3 within the above range, which helps to form a low-melting-point compound or liquid phase. The formation of the liquid phase helps the flow and contact between particles and promotes the formation of a sintering neck, thereby accelerating the sintering process and reducing the sintering temperature. This not only saves energy, but also reduces the degradation of material properties that may be caused by high-temperature sintering, such as abnormal grain growth and other problems. It is preferred to control the particle size of TiC particles within the above range, which helps to improve the microstructure of composite ceramics and enhance the strength and toughness of the material. It promotes the dispersion of TiC particles in the Al2O3 matrix, further inhibits the growth of Al2O3 grains, maintains the fine-grained structure of the material, and improves the hardness and resistance to crack propagation of the matrix. In addition, the high interfacial energy of TiC particles also helps to enhance the matrix and SiC w The bonding force between whiskers can reduce defects, thus helping to improve the comprehensive mechanical properties of composite ceramics.
[0033] In another typical embodiment of the present application, an Al2O3-SiC w-TiC composite ceramic preparation method, the preparation method comprises: the above-mentioned composition and solvent are sequentially mixed, dried and sintered to obtain Al2O3-SiC w -TiC composite ceramics.
[0034] The present invention first mixes the composition and the solvent, which helps to improve the dispersibility between the components, thereby facilitating uniform contact between the particles during the subsequent sintering process. The solvent is removed by drying, and the dried product is sintered to obtain Al2O3-SiC w -TiC composite ceramics. In addition, the preparation process of the present application is simple and suitable for industrial production.
[0035] In one embodiment of the present application, the preparation method further comprises: placing the dried product into a mold and then sintering it, and the mold is preferably a graphite mold.
[0036] In one embodiment of the present application, the sintering is carried out in a vacuum hot pressing sintering furnace, and the sintering temperature is 1600-1750°C; and / or the sintering holding time is 0.5-3h; and / or the sintering hot pressing pressure is 15-35MPa; and / or the drying temperature is 70-110°C; and / or the drying time is 6-15h; and / or the volume ratio of the composition to the solvent is 1:15-50; and / or the mixing includes: ultrasonicating and ball milling the composition and the solvent in sequence, and then drying.
[0037] The sintering process is carried out in a vacuum hot pressing sintering furnace, which can effectively reduce the pores and foreign impurities in the material, improve the density and purity of the material, and at the same time, the vacuum environment can reduce the oxidation effect of oxygen in the air on the material and maintain the original performance of the material. It is preferred to control the sintering temperature within the above range, which is helpful to make Al2O3, SiC w It reacts more fully with TiC and forms a dense structure. It is preferred to control the sintering holding time within the above range, which helps the material to have enough time for grain boundary diffusion and inter-particle bonding at high temperature, which is beneficial to the optimization of grain structure and the elimination of micro defects. Under lower pressure, the density of the material may be insufficient, while under too high pressure, it may cause an increase in internal stress of the material, affecting the performance and service life of the material. It is preferred to control the hot pressing pressure of sintering within the above range, which helps to further promote close contact and grain boundary diffusion between particles, and improve the density and flexural strength of the material. The preferred sintering vacuum is 8 to 12 Pa.
[0038] It is preferred to control the drying temperature and time within the above range, which helps to improve the efficiency of removing the solvent and avoid thermal decomposition or crystal transformation of the material due to excessive temperature during the drying process. Preferably, the drying is carried out in a blast drying oven. It is preferred to control the volume ratio of the composition and the solvent within the above range, which helps to fully disperse the composition in the solvent and reduce the probability of agglomeration. Preferably, the solvent is selected from any one or more of ethanol, sodium hexametaphosphate aqueous solution and ammonium citrate aqueous solution.
[0039] The composition and the solvent are sequentially subjected to ultrasonic dispersion and ball milling, which helps to fully disperse and evenly mix the composition powder to form a stable mixed solution. Ultrasonic dispersion helps to break the agglomeration of the composition powder, while ball milling further refines and homogenizes the mixture, which helps to improve the microstructure uniformity and micro-interface bonding strength of the composite ceramic, thereby helping to improve the fracture toughness and flexural strength of the composite ceramic.
[0040] In order to further improve the fracture toughness and flexural strength of the composite ceramic, in one embodiment of the present application, the ultrasonic time is preferably 30 to 60 minutes; and / or the ball milling time is 4 to 16 hours; and / or the ball milling speed is 250 to 500 rpm.
[0041] In another typical embodiment of the present application, an Al2O3-SiC w -TiC composite ceramics, the Al2O3-SiC w -TiC composite ceramics are prepared by the aforementioned preparation method.
[0042] The above Al2O3-SiC w -TiC composite ceramics have high fracture toughness and flexural strength.
[0043] In one embodiment of the present application, the Al2O3-SiC w -The fracture toughness of TiC composite ceramics is 5.1~7.2MPa·m 1 / 2 ; and / or, Al2O3-SiC w -The flexural strength of TiC composite ceramics is 436~595MPa.
[0044] Al2O3-SiC with the above fracture toughness and flexural strength w -TiC composite ceramics are more suitable as cutting tool materials.
[0045] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.
[0046] Example 1
[0047] (1) Prepare raw material powders. Weigh 15.8 g of Al2O3 powder and 3 g of SiC w powder, 1g of TiC powder (particle size is 500nm), and 0.2g of sintering aid (the mass ratio of MgO to Y2O3 is 1:1).
[0048] (2) Weigh the Al2O3 powder and SiC w The powder, TiC powder and sintering aid powder were mixed and placed in a beaker, and anhydrous ethanol was added in a volume ratio of powder to anhydrous ethanol of 1:30, and a mixed solution was obtained after ultrasonic dispersion for 30 minutes.
[0049] (3) The obtained mixed solution was ball-milled at a rotation speed of 380 rpm for 12 h, and then placed in a forced air drying oven and dried at 80° C. for 12 h to obtain a mixed powder.
[0050] (4) The mixed powder is loaded into a graphite mold, and then placed in a vacuum hot pressing sintering furnace, hot pressed and sintered in a vacuum atmosphere, and cooled to room temperature with the furnace after the insulation is completed. The diameter of the graphite mold is 30 mm, the sintering temperature is 1700°C, the hot pressing pressure is 30 MPa, the sintering vacuum degree is 8 Pa, and the insulation time is 2 h to obtain Al2O3-SiC w -TiC ceramic material.
[0051] Example 2
[0052] (1) Prepare raw material powders. Weigh 15.8 g of Al2O3 powder and 2 g of SiC w powder, 2g of TiC powder (particle size is 500nm), and 0.2g of sintering aid (the mass ratio of MgO to Y2O3 is 1:1).
[0053] (2) Weigh the Al2O3 powder and SiC w The powder, TiC powder and sintering aid powder were mixed and placed in a beaker, and anhydrous ethanol was added in a volume ratio of powder to anhydrous ethanol of 1:15, and a mixed solution was obtained after ultrasonic dispersion for 30 minutes.
[0054] (3) The obtained mixed solution was ball-milled at a rotation speed of 250 rpm for 12 h, and then placed in a forced air drying oven and dried at 80° C. for 12 h to obtain a mixed powder.
[0055] (4) The mixed powder is loaded into a graphite mold, and then placed in a vacuum hot pressing sintering furnace, hot pressed and sintered in a vacuum atmosphere, and cooled to room temperature with the furnace after the insulation is completed. The diameter of the graphite mold is 30 mm, the sintering temperature is 1600°C, the hot pressing pressure is 35 MPa, the sintering vacuum degree is 12 Pa, and the insulation time is 3 h to obtain Al2O3-SiC w-TiC ceramic material.
[0056] Example 3
[0057] (1) Prepare raw material powders. Weigh 15.8 g of Al2O3 powder and 1 g of SiC w powder, 3 g of TiC powder (particle size is 300 nm), and 0.2 g of sintering aid (the mass ratio of MgO to Y2O3 is 1:1).
[0058] (2) Weigh the Al2O3 powder and SiC w The powder, TiC powder and sintering aid powder were mixed and placed in a beaker, and anhydrous ethanol was added in a volume ratio of powder to anhydrous ethanol of 1:50, and a mixed solution was obtained after ultrasonic dispersion for 30 minutes.
[0059] (3) The obtained mixed solution was ball-milled at a rotation speed of 500 rpm for 12 h, and then placed in a forced air drying oven and dried at 80° C. for 12 h to obtain a mixed powder.
[0060] (4) The mixed powder is loaded into a graphite mold, and then placed in a vacuum hot pressing sintering furnace, hot pressed and sintered in a vacuum atmosphere, and cooled to room temperature with the furnace after the insulation is completed. The diameter of the graphite mold is 30 mm, the sintering temperature is 1750°C, the hot pressing pressure is 15 MPa, the sintering vacuum degree is 12 Pa, and the insulation time is 0.5 h to obtain Al2O3-SiC w -TiC ceramic material.
[0061] Example 4
[0062] (1) Prepare raw material powders. Weigh 13 g of Al2O3 powder and 3 g of SiC w powder, 3g of TiC powder (particle size 500nm), and 1g of MgO sintering aid.
[0063] (2) Weigh the Al2O3 powder and SiC w The powder, TiC powder and sintering aid powder were mixed and placed in a beaker, and anhydrous ethanol was added in a volume ratio of powder to anhydrous ethanol of 1:30, and a mixed solution was obtained after ultrasonic dispersion for 30 minutes.
[0064] (3) The obtained mixed solution was ball-milled at a rotation speed of 380 rpm for 12 h, and then placed in a forced air drying oven and dried at 80° C. for 12 h to obtain a mixed powder.
[0065] (4) The mixed powder is loaded into a graphite mold, and then placed in a vacuum hot pressing sintering furnace, hot pressed and sintered in a vacuum atmosphere, and cooled to room temperature with the furnace after the insulation is completed. The diameter of the graphite mold is 30 mm, the sintering temperature is 1700°C, the hot pressing pressure is 20 MPa, the sintering vacuum degree is 12 Pa, and the insulation time is 2 h to obtain Al2O3-SiC w -TiC ceramic material.
[0066] Example 5
[0067] (1) Prepare raw material powders. Weigh 14 g of Al2O3 powder and 3 g of SiC w powder, 2g of TiC powder (particle size 500nm), and 1g of Y2O3 sintering aid.
[0068] (2) Weigh the Al2O3 powder and SiC w The powder, TiC powder and sintering aid powder were mixed and placed in a beaker, and anhydrous ethanol was added in a volume ratio of powder to anhydrous ethanol of 1:30, and a mixed solution was obtained after ultrasonic dispersion for 30 minutes.
[0069] (3) The obtained mixed solution was ball-milled at a rotation speed of 380 rpm for 12 h, and then placed in a forced air drying oven and dried at 80° C. for 12 h to obtain a mixed powder.
[0070] (4) The mixed powder is loaded into a graphite mold, and then placed in a vacuum hot pressing sintering furnace, hot pressed and sintered in a vacuum atmosphere, and cooled to room temperature with the furnace after the insulation is completed. The diameter of the graphite mold is 30 mm, the sintering temperature is 1700°C, the hot pressing pressure is 20 MPa, the sintering vacuum degree is 12 Pa, and the insulation time is 2 h to obtain Al2O3-SiC w -TiC ceramic material.
[0071] Example 6
[0072] The difference from Example 1 is that SiC w The mass of the powder is 2.4g, the mass of the TiC powder is 1.6g, and the Al2O3-SiC w -TiC ceramic material.
[0073] Example 7
[0074] The difference from Example 1 is that the mass of Al2O3 powder is 14g, the mass of TiC powder is 2g, and the mass of Y2O3 sintering aid is 1g. Finally, Al2O3-SiC w -TiC ceramic material.
[0075] Example 8
[0076] The difference from Example 1 is that SiC w The mass of the powder is 1g, and the final Al2O3-SiC w -TiC ceramic material.
[0077] Example 9
[0078] The difference from Example 1 is that the mass of Al2O3 powder is 13g, the mass of TiC powder is 3g, and the mass of MgO sintering aid is 1g. Finally, Al2O3-SiC w -TiC ceramic material.
[0079] Example 10
[0080] The difference from Example 1 is that the particle size of TiC is 300nm, and the Al2O3-SiC w -TiC ceramic material.
[0081] Embodiment 11
[0082] The difference from Example 1 is that the particle size of TiC is 40nm, and the Al2O3-SiC w -TiC ceramic material.
[0083] Example 12
[0084] The difference from Example 1 is that the particle size of TiC is 600nm, and the Al2O3-SiC w -TiC ceramic material.
[0085] Embodiment 13
[0086] The difference from Example 1 is that the sintering temperature is 1600°C, the sintering holding time is 3h, and the sintering hot pressing pressure is 15MPa. Finally, Al2O3-SiC w -TiC ceramic material.
[0087] Embodiment 14
[0088] The difference from Example 1 is that the sintering temperature is 1750°C, the sintering holding time is 0.5h, and the sintering hot pressing pressure is 35MPa. Finally, Al2O3-SiC w -TiC ceramic material.
[0089] Embodiment 15
[0090] The difference from Example 1 is that the sintering temperature is 1800°C, the sintering holding time is 0.3h, and the sintering hot pressing pressure is 40MPa. Finally, Al2O3-SiC w -TiC ceramic material.
[0091] Example 16
[0092] The difference from Example 1 is that the mass ratio of MgO to Y2O3 is 4:1, and the final Al2O3-SiC w -TiC ceramic material.
[0093] Embodiment 17
[0094] The difference from Example 1 is that the mass ratio of MgO to Y2O3 is 1:4, and the final Al2O3-SiC w -TiC ceramic material.
[0095] Comparative Example 1
[0096] (1) Prepare raw material powders. Weigh 15.8 g of Al2O3 powder and 4 g of SiC w powder, 0.2 g of sintering aid (the mass ratio of MgO to Y2O3 is 1:1).
[0097] (2) Weigh the Al2O3 powder and SiC w The powder and the sintering aid powder were mixed and placed in a beaker, and anhydrous ethanol was added in a volume ratio of powder to anhydrous ethanol of 1:30, and a mixed solution was obtained after ultrasonic dispersion for 30 minutes.
[0098] (3) The obtained mixed solution was ball-milled at a rotation speed of 380 rpm for 12 h, and then placed in a forced air drying oven and dried at 80° C. for 12 h to obtain a mixed powder.
[0099] (4) The mixed powder is loaded into a graphite mold, and then placed in a vacuum hot pressing sintering furnace, hot pressed and sintered in a vacuum atmosphere, and cooled to room temperature with the furnace after the insulation is completed. The diameter of the graphite mold is 30 mm, the sintering temperature is 1700°C, the hot pressing pressure is 30 MPa, and the insulation time is 2 h to obtain Al2O3-SiC w Ceramic material.
[0100] Comparative Example 2
[0101] The difference from Example 1 is that the mass of Al2O3 powder is 10g, and the mass of SiC w The mass of the powder is 4g, the mass of TiC is 4g, the mass of the sintering aid is 2g, the particle size of TiC is 1μm, and the final Al2O3-SiC w -TiC ceramic material.
[0102] The ceramic material was processed to obtain several 3mm×4mm×20mm and 3.2mm×2mm×25mm specimens, and the following performance tests were performed:
[0103] (a) Flexural strength: 3 mm × 4 mm × 20 mm specimens were used to test the three-point flexural strength of Al2O3-based composite ceramics with a span of 10 mm. Three specimens were taken for each test and the results were averaged.
[0104] (b) Fracture toughness: 3.2 mm × 2 mm × 25 mm specimens were used to test the fracture toughness of the specimens using the single-edge notched beam method. The span was 15 mm and the notch size was 1.6 ± 0.32 mm. Three specimens were taken for each test and the results were averaged.
[0105] The flexural strength and fracture toughness of the ceramic materials prepared in the examples and comparative examples were tested. The test results are shown in Table 1.
[0106] Table 1
[0107] Implementation / Comparative Example <![CDATA[Fracture toughness / (MPa·m 1 / 2 )]]> Flexural strength / (MPa) Example 1 6.9 595 Example 2 6.8 514 Example 3 5.3 448 Example 4 5.8 499 Example 5 6.2 476 Example 6 6.8 517 Example 7 6.5 473 Example 8 5.3 436 Example 9 5.1 447 Example 10 7.0 582 Embodiment 11 7.2 523 Example 12 6.4 469 Embodiment 13 6.7 573 Embodiment 14 6.8 561 Embodiment 15 6.5 493 Example 16 6.7 564 Embodiment 17 6.2 482 Comparative Example 1 7.0 397 Comparative Example 2 5.3 377
[0108] It can be seen from Table 1 that Al2O3-SiC w Adding TiC particles to ceramic materials can significantly improve the flexural strength of composite ceramics; w -TiC, 7.0MPa·m 1 / 2 ) has a fracture toughness comparable to that of Comparative Example 1 (Al2O3-SiC w , 6.9MPa·m 1 / 2 ) is equivalent to that of the steel sheet, but the flexural strength increases from 397MPa to 595MPa, an increase of nearly 50%, achieving a good reinforcement effect.
[0109] Figure 1 This is a SEM photo of the fracture of the ceramic material in Example 1 of the present application. Figure 2 This is a SEM photo of the fracture of the ceramic material in Example 2 of the present application. Figure 3 This is a SEM photo of the fracture of the ceramic material in Example 3 of the present application. Figure 4 This is a SEM photo of the fracture of the ceramic material in Comparative Example 1 of the present application. Figure 1 , Figure 2 , Figure 3 and Figure 4 It can be seen from the comparison that Figure 1 , Figure 2 and Figure 3 The grain size of Al2O3 matrix is smaller than Figure 4 The grain size of the Al2O3 matrix in the composite ceramics is shown in Figure 2, indicating that the addition of TiC particles can reduce the grain size of the Al2O3 matrix and strengthen the grain boundary strength, thereby improving the flexural strength of the Al2O3-based composite ceramics. Figure 4 The fracture mode of ceramic materials is transgranular fracture, while Figure 1 , Figure 2 and Figure 3 The ceramic material exhibits a fracture mode in which intergranular / transgranular fracture coexists, and the crack propagation path is relatively tortuous, which can consume more fracture work and thus obtain higher fracture toughness.
[0110] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0111] The introduction of TiC particles with a particle size of no more than 800nm helps to improve the flexural strength of the composite ceramic. TiC particles can inhibit the growth of Al2O3 matrix grains, forming a fine and evenly distributed grain structure, which is conducive to enhancing the strength of the material. At the same time, the excellent interface bonding between TiC and the Al2O3 matrix can effectively transfer loads and avoid crack propagation, thereby helping to improve the flexural performance of the composite ceramic. Normally, the addition of TiC easily leads to an increase in the brittleness of the ceramic, but the addition of TiC particles in this application is similar to that of SiC. w The synergistic effect of TiC particles can improve the fracture toughness of composite ceramics. The presence of TiC particles in the crack path can induce crack deflection, bridging and pinning effects, which in turn helps to increase the energy barrier for crack propagation, making it less likely for composite ceramics to undergo brittle fracture when subjected to external forces. w The mass proportion of TiC particles is within the above range, which helps to improve the interaction between the components, thereby helping to further improve the Al2O3-SiC w -Fracture toughness and flexural strength of TiC composite ceramics.
[0112] The above are only embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A kind of Al2O3-SiC w -TiC composite ceramic composition, characterized in that In terms of mass percentage, the composition comprises: 5-15wt% SiC w ; 5 to 15 wt% TiC particles; and The balance is Al2O3; wherein the particle size of the TiC particles does not exceed 800nm.
2. The composition according to claim 1, characterized in that In terms of mass percentage, the composition comprises: 10 to 15 wt% of the SiC w , 5 to 10 wt % of the TiC particles and the balance of the Al2O3.
3. The composition according to claim 1 or 2, characterized in that The Al2O3, the SiC w The mass ratio of the TiC particles to the TiC particles is 0.79:(0.1-0.15):(0.05-0.1); and / or, the composition further comprises 1-5wt% of a sintering aid.
4. The composition according to claim 3, characterized in that The sintering aid is MgO and / or Y2O3; and / or the particle size of the TiC particles is 40 to 500 nm.
5. The composition according to claim 4, characterized in that The sintering aid is a combination of the MgO and the Y2O3, and the mass ratio of the MgO to the Y2O3 is 1-4:1; and / or the particle size of the TiC particles is 300-500 nm.
6. A Al2O3-SiC w -A method for preparing TiC composite ceramics, characterized in that: The preparation method comprises: The composition according to any one of claims 1 to 5 and a solvent are sequentially mixed, dried and sintered to obtain the Al2O3-SiC w -TiC composite ceramics.
7. The preparation method according to claim 6, characterized in that: The sintering is carried out in a vacuum hot pressing sintering furnace, the sintering temperature is 1600-1750° C.; and / or, the sintering holding time is 0.5-3 h; and / or, the hot pressing pressure of the sintering is 15-35 MPa; And / or, the drying temperature is 70-110°C; and / or, the drying time is 6-15h; and / or, the volume ratio of the composition to the solvent is 1:15 to 50; And / or, the mixing includes: subjecting the composition and the solvent to ultrasonic treatment and ball milling in sequence, and then subjecting the composition and the solvent to drying.
8. The preparation method according to claim 7, characterized in that: The ultrasonication time is 30 to 60 minutes; and / or, the ball milling time is 4 to 16 hours; and / or, the ball milling speed is 250 to 500 rpm.
9. A kind of Al2O3-SiC w -TiC composite ceramic, characterized in that The Al2O3-SiC w -TiC composite ceramics are prepared by the preparation method described in any one of claims 6 to 8.
10. Al2O3-SiC according to claim 9 w -TiC composite ceramic, characterized in that The Al2O3-SiC w -The fracture toughness of TiC composite ceramics is 5.1~7.2MPa·m 1 / 2 ; and / or, the Al2O3-SiC w -The flexural strength of TiC composite ceramics is 436~595MPa.
Citation Information
Patent Citations
Preparation method of SiC whisker toughened alumina ceramic cutter material
CN114956846A